Study on optimization of secondary suspension parameters of double suspension maglev train - XU Yilan; MA Weihua; ZHANG Shuo; ZHANG Min; LUO Shihui (机车电传动)
As a key component of the vehicle's secondary suspension, the performance of air springs directly affects the comfort and safety of the vehicle. Using a double suspension frame module with mid-set air springs as the research object, the light tourist maglev train dynamic model was established, and comparing the dynamic performance under different horizontal and vertical stiffness conditions, according to the comfort, safety and structural requirements of the vehicle, the optimal range of air spring horizontal stiffness and vertical stiffness was analyzed, as well as the influence of different vehicle body mass center heights on the selection of air spring stiffness. The results show that as the height of the center of mass of the vehicle body increases, the required horizontal stiffness of the air spring increases correspondingly, but the selection of the vertical stiffness has no obvious effect on it.